2015
DOI: 10.1080/15548627.2015.1112484
|View full text |Cite
|
Sign up to set email alerts
|

GADD45A inhibits autophagy by regulating the interaction between BECN1 and PIK3C3

Abstract: Abbreviations: ACTB/b-actin, actin, beta; ATG, autophagy-related, Baf, bafilomycin A 1 ; BECN1, Beclin 1, autophagy related; DAPI, 4 0 ,6-diamidino-2-phenylindol dihydrochloride; DNA, deoxyribose nucleic acid; GADD45A, growth arrest and DNA-damage-inducible, alpha; GFP, green fluorescent protein; GST, glutathione s-transferase; LC3/MAP1LC3, microtubule-associated protein 1 light chain 3; MEFs, mouse embryonic fibroblasts; MTOR, mechanistic target of rapamycin (serine/threonine kinase); PIK3C3, phosphatidylinos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…LC3‐II expression is increased in Gadd45a‐knockout cells but is decreased in cells that overexpress Gadd45a. It was also reported that Gadd45a can disrupt the formation of Becn1 and the phosphatidylinositol 3‐kinase complex that is required for the initiation of autophagy 34 . Another study showed that the mRNA levels of Gadd45a expression were increased while protein levels were decreased in diabetic hearts 47 .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…LC3‐II expression is increased in Gadd45a‐knockout cells but is decreased in cells that overexpress Gadd45a. It was also reported that Gadd45a can disrupt the formation of Becn1 and the phosphatidylinositol 3‐kinase complex that is required for the initiation of autophagy 34 . Another study showed that the mRNA levels of Gadd45a expression were increased while protein levels were decreased in diabetic hearts 47 .…”
Section: Discussionmentioning
confidence: 96%
“…ROS are generally considered to be one of the main inductors of autophagy, which is activated to reduce oxidative stress 33 . Becn1, a gene required to initiate the formation of autophagosome in autophagy, 34 contributes to cellular homeostasis by regulating autophagy, also participating in the classification of vacuolar proteins and apoptosis. Besides this, it plays a protective role against neurodegenerative and cardiac diseases 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CPCGI also suppressed the expression of GADD45α, a protein that has been shown to activate apoptosis by inducing the translocation of BCL2L11/Bim from the cytoskeleton to the mitochondria 41. Interestingly, GADD45α has also been shown to inhibit autophagy by directly interacting with Beclin1,42 suggesting that CPCGI might induce autophagy as a protective mechanism in the ischemic cortex. The results were in accordance with our previous data.…”
Section: Discussionmentioning
confidence: 97%
“…As such GADD45A and GADD45B were significantly increased after spautin‐1 treatment. These two proteins were targets of DNA damage, and they played critical roles in apoptosis and G2/M checkpoint in response to DNA damage . In addition, BTG2, a cell cycle control gene, initiated the G2/M phase arrest and inhibited cell growth and was induced in response to DNA damage mediated by p53‐dependent mechanisms .…”
Section: Discussionmentioning
confidence: 99%